A survey of larval digeneans in the commonest intertidal snails from Northern Patagonian coast, Argentina - Gilardoni, Carmen Mariangel (2011)
Over a two-years period, a survey was carried out in order to increase the knowledge of digeneans parasitising the commonest intertidal gastropods on the Patagonian coast, Southwestern Atlantic Ocean. A total of 4,725 gastropods were examined. Six species of digenean parasitising four snail species were found; four of them were registered for first time: Maritrema sp. 1 (Microphallidae) in Crepidula dilatata (Calyptraeidae), Parorchis sp. (Philophtalmidae) and sporocyst of Renicolidae in Trophon geversianus (Muricidae), and Diphterostomum sp. (Zoogonidae) in Buccinanops globulosus (Nassariidae). Two other species were found in Siphonaria lessoni (Siphonariidae): Maritrema sp. 2 and Hemiuridae. One snail species, Tegula patagonica (Trochidae) was not parasitised. These gastropods act as first intermediate host, and C. dilatata, S. lessoni and B. globulosus also frequently host metacercariae within the sporocyst. Overall prevalences varied from 0.16% of Diphterostomum in the intertidal population of B. globulosus to 33.45% of Maritrema sp. 1 in C. dilatata.